Ontology and Ecclesiology in the Apocalypse - Minear, Paul Sevier (New Testament studies, 1966)
You may be surprised at the first term in my topic: ontology. Should a biblical interpreter deal with such a topic? Is he obliged to clarif the ontological assertions and assumptions of the biblical writers? From our colleagues in other disciplines we hear differing answers to this question. Some philosophers demand from us greater concern with ontology. Others warn us against such concern. Still other philosophers, absorbed in the discoveries of linguistic analysis, repudiate even for themselves the legitimacy of ontological statements. Whether it is encouragement or discouragement that we receive from our academic colleagues, it must be admitted that few biblical scholars are willing to venture into this realm.